SISTEM PENCATATAN DAN PELAPORAN TERPADU PUSKESMAS (SP2TP) DI WILAYAH DINAS KESEHATAN KABUPATEN DOMPU PROVINSI NTB - Suryani, Nurul Dwi; Solikhah, Solikhah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2013)
AbsractBackground: SP2TP is to meet the needs of administration at the higher level in order to develop, determine policies and utilized by health centers to improve efforts of health centers, through planning, mobilization, execution, monitoring, control and assessment. Based on the results of the initial survey SP2TP in Dompu has not been maximal. Therefore it is necessary to study the system of integrated recording and reporting of health centers (SP2TP) in the area of health services in Dompu Regency.Methods: This research is a qualitative descriptive located in all district health centers in Dompu Regency. Data was collected through interviews with the study subjects of ten people in the board of integrated recording and reporting system of health centers in each health center and health department.Results: The study results indicated that the reporting was still done manually; it still focused ondisease patterns and the most 10 diseases. The submitted report was incomplete because there was no coordination, guiding book, difficult transportation, electrical disturb, Feedback was given orally. In terms of data quality SP2TP was still low. This was proven by the low completeness and timeliness for report delivery. While the use of data and information was still focused on the annual profiling.Conclusion: the difficult accessibility of health centers with the Health Service made report shipping incomplete and not timely.Â Keywords: System reporting, system recording, SP2TP